Analysis of Factors that Influence Consumer Loyalty in Purchasing Vegetables at the Panorama Spill Market in Bengkulu City - Indriani, Desy; Irnad, Irnad; Sumantri, Bambang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the level of loyalty and what factors influence the loyalty of vegetable consumers at The Panorama Spill Market, Bengkulu City. This research was conducted during June-July 2024. The data collection methods used are secondary data and primary data. Where primary data is obtained from direct interviews with 100 traders (virtucio formula). The data analysis method used is structural equation modeling (SEM) analysis to answer the problem formulation. The results showed that the level of consumer satisfaction in purchasing vegetables in the panorama spill market of Bengkulu City had a satisfied category. The level of consumer loyalty in purchasing vegetables in the panorama spill market of Bengkulu City has a loyal category. The results of the direct analysis show that price and product quality affect customer satisfaction and customer satisfaction and service quality affect product loyalty. In addition, the indirect effect states that price and product quality affect consumer loyalty through customer satisfaction.